HUBUNGAN MOBILISASI DINI DAN PERSONAL HYGIENE DENGAN PENYEMBUHAN LUKA PERINEUM PADA IBU NIFAS DI PMB ANITA.AB KABUPATEN OKU - Sari, Dian Puspita; Winarni, Winarni (Seroja Husada: Jurnal Kesehatan Masyarakat, 2025)
Background: Perineal wounds are commonly experienced during the first delivery but can also occur in subsequent deliveries. According to WHO data (2024), there were nearly 2.7 million cases of perineal tears among delivering mothers in Indonesia. Perineal wound healing can be addressed through non-pharmacological therapies, such as early mobilization and personal hygiene. Early mobilization helps improve blood circulation and accelerate the healing process of perineal wounds, while personal hygiene maintains the cleanliness of the genital area and prevents infection. Both play an important role in speeding up postpartum recovery and reducing the risk of complications. Objective: To determine the relationship between early mobilization and personal hygiene with perineal wound healing in postpartum mothers at PMB Anita.AB, OKU Regency, in 2025. Methods: This study used a quantitative analytic method with a cross-sectional approach. Results: The frequency distribution of perineal wound healing showed that most respondents experienced normal healing, with 15 respondents (41.7%). Most respondents practiced good early mobilization, totaling 21 respondents (58.3%), and 17 respondents (47.2%) performed adequate personal hygiene. Statistical test results kolmogorov smirnov showed a significant relationship between early mobilization (p-value = 0.023) and personal hygiene (p-value = 0.027) with perineal wound healing at PMB Anita.AB, OKU Regency, in 2025. Conclusion: There is a relationship between early mobilization and personal hygiene with perineal wound healing at PMB Anita.AB, OKU Regency, in 2025.